Pengaruh Pengungkapan Enterprise Risk Management dan Pengungkapan Intellectual Capital Terhadap Nilai Perusahaan dengan Good Corporate Governance Sebagai Moderasi - Astina Elisabeth S Emar; Sri Ayem (Universitas Warmadewa, 2020)
The purpose of this study was to know the impact of enterprise risk management (ERM) disclosure and intellectual capital (IC) disclosure to the company’s value with good corporate governance (GCG) as the moderate variable. The sample in this study were manufacturing companies listed on the Indonesian Stock Exchange (IDX) in 2016-2018 with total of 66 companies based on purposive sampling method. The analysis technique used is linear regression and moderated regression analysis (MRA). The study results indicated that ERM disclosure does not affect the company’s value and IC disclosure has a significance positive effect on company’s value, while GCG variables are unable to moderate the effect of ERM disclosure on company’s value and GCG can strengthen the effect of IC disclosure to the company’s value.